Water Quality Characterization of Varsity Lake, University of Malaya, Kuala Lumpur, Malaysia - M. Aqeel Ashraf; M. Jamil Maah; Ismail Yusoff (E-Journal of Chemistry)
Lakes and reservoirs are important sources of water supply, generate electricity and to irrigate fields. Since, lakes act as catchment basins for close to 40% of the landscape so serve as recreational, sporting and fishing activities. Varsity Lake University of Malaya (UM) is beautiful landscape at the front of the UM main entrance. It is used mainly for recreational and sporting (canoeing) activities. Study has been carried out in order to analyze water quality, nutrients and metals load starting from water inlets into the lake basin. It was found that there is high concentration of oil and grease particles in water due to water flow from cafeteria of college 2, engineering and built environment faculties which cause BOD and TSS value to be higher then normal in the lake. It was one of the main factors that caused the death of fish in the lake in recent months. Mercury and nitrate concentration is also high in the lake. A body contact is involved due to sporting and recreational activities so parameters are compared with Malaysian Interim water quality standards and it was concluded that lake water quality is not fulfilling the recreational spot criteria and is hazardous to human and fish life in the lake. Recommendations are proposed for immediate action. Best management practices is also discussed for prevention of oil and grease particles from entry into lake water to protect this valuable water resource from being polluted.